Restoration of vascular dysfunction resulting from maternal high-fat diet via modulation of the NLRP3/IL-1β axis - Yuxuan Xiao; Xianru Bi; Rongjie Zhang; Yu Li; Wei Sun; Yingxue Hao (Clinical and Experimental Hypertension)
This study investigated the impact of maternal high-fat diet on vascular function and endothelial homeostasis in offspring. We found that offspring exposed to maternal high-fat diet exhibited elevated blood pressure, impaired abdominal aortic vascular function, and endothelial homeostasis imbalance. These changes were accompanied by increased levels of reactive oxygen species (ROS) and upregulation of pro-inflammatory cytokines (including IL-1β, TNF-α, IL-6, and IL-10). Treatment with NLRP3 or IL-1β inhibitors prevented the deterioration in vascular function, reduced endothelial NO production, and inflammation induced by maternal high-fat diet exposure compared to the control group. The findings suggest that during pregnancy, mitigating the vascular impairments in offspring induced by maternal high-fat diet can be achieved by inhibiting the NLRP3/IL-1β pathway.